Dehydroascorbic acid, the oxidized form of vitamin C, improves renal histology and function in old mice. Issue 12 (21st May 2020) - Forman, Katherine; Martínez, Fernando; Cifuentes, Manuel; Fernández, Marcos; Bertinat, Romina; Torres, Pablo; Salazar, Katterine; Godoy, Alejandro; Nualart, Francisco
Abstract: Oxidative stress and inflammation are crucial factors that increase with age. In the progression of multiple age‐related diseases, antioxidants and bioactive compounds have been recognized as useful antiaging agents. Oxidized or reduced vitamin C exerts different actions on tissues and has different metabolism and uptake. In this study, we analyzed the antiaging effect of vitamin C, both oxidized and reduced forms, in renal aging using laser microdissection, quantitative reverse‐transcription polymerase chain reaction, and immunohistochemical analyses. In the kidneys of old SAM mice (10 months of age), a model of accelerated senescence, vitamin C, especially in the oxidized form (dehydroascorbic acid [DHA]) improves renal histology and function. Serum creatinine levels and microalbuminuria also decrease after treatment with a decline in azotemia. In addition, sodium‐vitamin C cotransporter isoform 1 levels, which were increased during aging, are normalized. In contrast, the pattern of glucose transporter 1 expression is not affected by aging or vitamin C treatment. We conclude that oxidized and reduced vitamin C are potent antiaging therapies and that DHA reverses the kidney damage observed in senescence‐accelerated prone mouse 8 to a greater degree. Abstract : We conclude that oxidized and reduced vitamin C are potent antiaging therapies and that DHA reverses the kidney damage observed in SAMP8 mice to a greater degree.